Interstitial eosinophilic aggregates in diabetic nephropathy: allergy or not?. Issue 8 (25th March 2015) - Dai, Dao-Fu; Sasaki, Kotaro; Lin, Mercury Y.; Smith, Kelly D.; Nicosia, Roberto F.; Alpers, Charles E.; Najafian, Behzad
Abstract : Background: Interstitial eosinophilic aggregates (IEA) in renal biopsies often suggest allergic tubulointerstitial nephritis, yet clear associations with drug reactions are often difficult to establish. IEA are also encountered in diabetic nephropathy (DN) and thought to be attributed to medication exposure. Methods: Native medical kidney biopsies performed at the University of Washington Medical Center were reviewed, including DN ( n = 64), IgA nephropathy (IgAN, n = 28), membranous nephropathy (MN, n = 14), focal and segmental glomerulosclerosis (FSGS, n = 27) and membranoproliferative glomerulonephritis (MPGN, n = 28). IEA were defined as ≥5 eosinophils per high power field. The severity of interstitial fibrosis and tubular atrophy (IFTA) was scored semi-quantitatively as minimal, mild, moderate or severe. Results: IEA were remarkably more prevalent in DN (41%), when compared with IgAN (7%, P = 0.001), MN (8%, P = 0.017) or MPGN (14%, P = 0.013), but not FSGS (26%, P = 0.18). In DN cases, univariate analysis revealed that IEA were associated with greater IFTA severity, but not with the percentage of glomerulosclerosis, mesangial expansion, history of drug allergy, number of prescribed medications or particular class of medications (antibiotics, NSAIDs, aspirin, thiazide, loop diuretics, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, calcium channel blockers, beta blockers, insulin, sulfonylurea, metformin or allopurinol). Multivariate analysis showed that the severity of IFTA was the only significant predictor for IEA (P < 0.01) after stepwise adjustment for age, number of medications, drug allergy, diabetes type, % global glomerulosclerosis and mesangial expansion. Conclusions: Our study shows that IEA are more common in DN, when compared with other types of glomerulopathy. In DN, IEA are associated with the severity of IFTA but not with prescribed medications or clinical history of allergy. This suggests that in DN IEA are often associated with chronic tubulointerstitial injury and are not diagnostic of an allergic interstitial nephritis.